JUNIOR HIGH SCHOOL STUDENTS’ READING HABIT AND MOTIVATION DURING THE IMPLEMENTATION OF KURIKULUM MERDEKA - Anastasia Ronauli Hasibuan; Ira Irzawati; Siti Rahma Ayu (TELL - US JOURNAL, 2025)
The spirit of Kurikulum Merdeka provides big opportunity for students to gain more learning experience and develop their self-potential. This curriculum highlights the freedom to achieve many things during the learning period. The innovation can even prove an increase of students’ literacy achievement in Indonesia. Reading habits and motivation are one of the elements that contribute to improve literacy. This research explored the relationship between students’ reading habits and motivation during the implementation of Kurikulum Merdeka. This correlational study involved seventeen students of English Club members of a Junior High School in Palembang. They were selected by using convenience sampling technique. The data were collected through two types of questionnaires, namely Reading Habits and Reading Motivation Questionnaires. The obtained data were analyzed through Pearson Product Moment formula. The results showed that the mean scores of reading habit and reading motivation were 2.92 and 128.94 descriptively. Most students were at the moderate level of reading habit with the percentage of 58.8% (10 students). In addition, fourteen students (82.4%) were at the medium level of reading motivation. The correlational test also revealed that the pearson correlation value was 0.651 with the significance level of 0.005. The output of pearson correlation value showed positive coefficient value which means higher the degree of students’ reading habit level, the higher their reading motivation level is. It is expected that the results of this research brings a new perspective that is potentially used as the source of reference and information especially for the readers.